Tectonic setting of Middle Devonian to Lower Carboniferous rocks in the Magdalen Basin - Durling, P.; Marillier, F. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1993)
Seismic reflection data in the Gulf of St. Lawrence were used to construct an isopach map of the Horton Group (Middle Devonian-Early Carboniferous) in the Magdalen Basin. The map shows that the Horton Group was deposited in basins that developed parallel to the offshore extension of structural trends in New Brunswick and the Gaspe Peninsula. Horton Group strata were deposited in narrow linear fault bounded basins, presently up to 8 km deep, and in broad sag basins up to 3 km deep. The sag basins may thin latterally to form sedimentary veneers less than 1 km thick. The fault bounded basins are mostly half-grabens and they developed during an early crustal extension phase. The largest and deepest basin strikes northeast-southwest, almost parallel to the Moncton Basin in New Brunswick. Sag basins and thin veneers are not fault controlled and are widespread, underlying most of the Magdalen Basin. They probably formed later than the fault bounded basins in response to the onset of a regional subsidence phase. Deformation of Horton Group rocks in the Magdalen Basin is concentrated in fault zones up to 20 km wide, and mainly affected deep subbasins, where thrust faults and possible flower structures are observed. An early deformation phase occurred towards the end of Horton Group sedimentation (Late Tournaisian-Early Visean) and a later phase occurred, with less intensity, during the deposition of Visean to ?Namurian sediments. The first phase of deformation affected most of the Magdalen Basin, whereas the second phase affected mainly the southern areas.